Death After Poison Ivy Smoke Inhalation. (13th December 2022) - Woolery, Samantha; Willner, Joseph; Prahlow, Joseph A.; Douglas, Elizabeth
Abstract: Urushiol, the active antigen in poison ivy ( Toxicodendron radicans ), is frequently associated with type I and type III hypersensitivity reactions. These reactions most often result in cutaneous symptoms that vary in severity and may at times require medical interventions. Injuries involving other body systems associated with urushiol exposure are far less common. Here, we present 2 unrelated cases of urushiol respiratory exposure status after burning of poison ivy that resulted in cardiopulmonary arrest and ultimately death. In both cases, the history, circumstances, and autopsy findings are consistent with urushiol smoke inhalation having either caused or contributed to death. The cases are unique in that they represent the first cases of death related to poison ivy smoke exposure. Clinicians and forensic pathologists should be aware of the fact that urushiol smoke exposure may lead to morbidity and mortality.